Hydrocortisone dosing in children with classic congenital adrenal hyperplasia: results of the German/Austrian registry - Hoyer-Kuhn, Heike-Katharina; Huebner, Angela; Richter-Unruh, Annette; Bettendorf, Markus; Rohrer, Tilman; Kapelari, Klaus; Riedl, Stefan; Mohnike, Klaus; Dörr, Helmuth-Günther; Roehl, Friedrich-Wilhelm; Fink, Katharina; Holl, Reinhard W.; et al. (Endocrine Connections, 2021)
Treatment of classic congenital adrenal hyperplasia (CAH) is necessary to compensate for glucocorticoid/mineralocorticoid deficiencies and to suppress androgen excess. Hydrocortisone (HC) is preferred in growing children with classic CAH but recommendations regarding dosage/administration are inconsistent. The aim of this study was to evaluate HC dosing in children with CAH in relation to chronological age, sex, and phenotype based on a multicenter CAH registry.